A novel fuzzy approach to evaluate the quality of examination timetabling - Asmuni, Hishammuddin; Burke, Edmund K.; Garibaldi, Jonathan M.; McCollum, Barry (Springer Verlag, 2007)
In this paper we introduce a new fuzzy evaluation function for examination timetabling. We describe how we employed fuzzy reasoning to evaluate the quality of a constructed timetable by considering two criteria: the average penalty per student and the highest penalty imposed on any of the students. A fuzzy system was created based on a series of easy to understand rules to combine the two criteria. A significant problem encountered was how to determine the lower and upper bounds of the decision criteria for any given problem instance, in order to allow the fuzzy system to be fixed and, hence, applicable to new problems without alteration. In this work, two different methods for determining boundary settings are proposed. Experimental results are presented and the implications analysed. These results demonstrate that fuzzy reasoning can be successfully applied to evaluate the quality of timetable solutions in which multiple decision criteria are involved.